Tanggung Jawab Notaris Pengganti dalam Pembuatan Akta - Henny Saida Flora (Kanun Jurnal Ilmu Hukum, 2012)
ABSTRACT: A public notary has an authority as a notary as an officer as mentioned in the Act of Public Notary in Article 1 Number 3 that is a public officer pointed for a temporary time and has the power as notary. A replacement notary is appointed by compentent officer based on the act not by the notary who refers him. The rule on the legal status of the replacement notary is needed not only for the interest of the notary, but also for public who needs the notary. The Responsibility of Replacement Public Notary in Making Authentic Document